Physico – Chemical And Biological Characterization Of Egg Drop Syndrome – 1976 (Eds –’76) Virus - Suresh, P.; Shoba, K.; Rajeswar, J. Johnson (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The Egg Drop Syndrome – 1976 (EDS –’76) virus isolate was characterized by physico-chemical and biological properties. The isolate withstood the chloroform (15 min), ethyl ether treatments (18 hr) and acidic pH (pH 3) for 1h. The isolate was resistant to 0.5 per cent trypsin treatment for 30 min and stable at 56o c for 40 min. The isolate lost its infectivity titer but not the HA activity when treated with 0.3 per cent formalin for 1h. The biological property was studied by infecting the isolate in duck embryo fibroblast monolayer and by appearance of cytopathogenicity like rounding and refractile cells. The peak CPE was noticed between 72 and 96 h post infection.
Keywords: Egg Drop Syndrome; 1976 (EDS –’76) virus; Avian adenovirus; Physico- chemical characters; Duck embryo fibroblast culture